The Main Issues of the Relationship Between the Servicing of the Economy and the Quality of Life of the Population of the Region - Juraeva, Dildora (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article reveals the main issues related servicing of the economy and the quality of life of the population of the region.